Analysis and identification of PTBP2 as an oncogene in hepatocellular carcinoma - Yuxuan Li; Fengguang Zhai; Lili Kong; Jie Zhu; Hong Li; Xiaofeng Jin (Discover Oncology)
Abstract Purpose Liver cancer, also known as hepatocellular carcinoma (HCC), is one of the most prevalent and lethal malignancies in the world. The management of HCC depends on the underlying hepatic function and histological stage of the neoplasm, potentially encompassing locoregional therapies, surgical resection, hepatic transplantation, targeted drug therapies, and immunotherapy. However, the outlook for advanced HCC remains poor, with global 5-year survival rates below 15%. Consequently, it is imperative to identify novel tumor biomarkers for HCC prediction. Methods Multiple public databases were used to analyze PTBP2 expression, potential biological functions, and immune infiltration levels in HCC. In addition, immunohistochemical staining, phenotypic experiments, flow cytometry, and mouse subcutaneous tumors were used to verify the elevated PTBP2 expression and its oncogenic effect in HCC. Results The expression of PTBP2 is abnormally high in liver cancer and promoted the occurrence and development of HCC. Conclusions Our study demonstrated that HCC tissues exhibited increased levels of PTBP2 expression compared to normal liver tissues. Elevated PTBP2 expression has been identified as closely linked to low survival in patients with HCC and could be a clinically independent prognostic factor. Additionally, PTBP2 may influence the development and forecasting of patients with HCC by altering the TME. Moreover, we confirmed the association between PTBP2 expression and HCC, both in vivo and in vitro.